Risk factors for lower limb lymphedema after lymph node dissection in patients with ovarian and uterine carcinoma - Tada, Harue (BioMed Central, 2009)
BACKGROUND: Lymph node dissection has proven prognostic benefits for patients with ovarian or uterine carcinoma; however, one of the complications associated with this procedure is lymphedema. We aimed to identify the factors that are associated with the occurrence of lymphedema after lymph node dissection for the treatment of ovarian or uterine carcinoma. METHODS: A total of 694 patients with histologically confirmed ovarian (135 patients) or uterine cancer (258 with cervical cancer, 301 with endometrial cancer) who underwent lymph node dissection were studied retrospectively. Logistic regression analyses were used to identify the risk factors associated with occurrence of lymphedema. RESULTS: Among ovarian and uterine cancer patients who underwent pelvic lymph node dissection, post-operative radiotherapy (odds ratio: 1.79; 95% confidence interval: 1.20–2.67; p = 0.006) was statistically significantly associated with occurrence of lymphedema. CONCLUSION: There was no relationship between any surgical procedure and occurrence of lymphedema among patients undergoing pelvic lymphadenectomy. Our findings are supported by a sound biological rationale because they suggest that limb lymphedema is caused by pelvic lymph node dissection.